Mass spectrometry imaging of Arabidopsis thaliana with in vivo D2O labeling - Na, Sumin; Lee, Young Jin (Frontiers in Plant Science, 2024)
Commonly used analytical tools for metabolomics cannot directly probe metabolic activities or distinguish metabolite differences between cells and sub-organs in multicellular organisms. These issues can be addressed by in vivo isotope labeling and mass spectrometry imaging (MSI), respectively, but the combination of the two, a newly emerging technology we call MSIi, has been rarely applied to plant systems. In this study, we explored MSIi of Arabidopsis thaliana with D2O labeling to study and visualize D-labeling in three classes of lipids: arabidopsides, chloroplast lipids, and epicuticular wax. Similar to other stress response, D2O induced stress increased arabidopsides in an hour but it was relatively minor for matured plants and reverted to normal level in a few hours. The D-labeling isotopologue patterns of arabidopsides were matching with those of galactolipid precursors, supporting the currently accepted biosynthesis mechanism. Matrix-assisted laser desorption/ionization (MALDI)-MSI was used to visualize the spatiotemporal distribution of deuterated chloroplast lipids, pheophytin a, MGDGs, and DGDGs, after growing day-after-sowing (DAS) 28 plants in D2O condition for 3-12 days. There was a gradual change of deuteration amount along the leaf tissues and with a longer labeling time, which was attributed to slow respiration leading to low D2O concentration at the tissues. Finally, the deuterium incorporation in epicuticular wax was visualized on the surfaces of stem and flower. The conversion efficiency of newly synthesized C30 aldehyde to C29 ketone was very low in the lower stem but very high at the top of stem near the flower or on the flower carpel. This study successfully demonstrated that MSIi can unveil spatiotemporal metabolic activities in various tissues of A. thaliana.